Dietary Vitamin C Intake Is Associated With Improved Liver Function and Glucose Metabolism in Chinese Adults - Luo, Xiaoqin; Zhang, Wanyu; He, Zhangya; Yang, Hexiang; Gao, Jiayi; Wu, Pei; Ma, Zheng Feei (Frontiers in Nutrition, 2022)
Background Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases worldwide. Dietary vitamin C intake might play an important role in reducing the risk of NAFLD. This study assesses the relationship between dietary vitamin C intake and diagnostic biomarkers of NAFLD. Methods The data from the 2009 China Health and Nutrition Survey (CHNS), nine provinces across four diverse regions (Northeast, East Coast, Central, and West) were included in the study. The dietary vitamin C intake of participants was calculated based on 3-day 24-h diet questionnaires at the individual level. The associations of dietary vitamin C intake and the biochemical indicators of liver function and glucose/lipid metabolism were determined. Results A total of 8,307 participants were included in the final analysis. The mean dietary vitamin C intake for the overall, male and female subjects was 79.8 ± 58.6, 81.6 ± 55.3, and 78.2 ± 61.2 mg/day, respectively. The prevalence of inadequate dietary vitamin C intake for the overall, male and female subjects was 24.4, 26.5, and 22.6%, respectively. Intake of vitamin C was associated with both lower concentrations of plasma ferritin and hemoglobin A1c (HbA1c). Higher dietary vitamin C intake was associated with higher albumin, even further adjusted for body mass index (BMI), residence, and smoking status. No improvement in lipid metabolism was found. Conclusion This study demonstrated that higher dietary vitamin C intake is a benefit for improving glucose metabolism and liver function in which reducing ferritin, a biomarker of iron accumulation, may be involved.